Therapist interventions and client innovative moments in emotion-focused therapy for depression - Cunha, Carla (2012)
According to the narrative approach, change in self-narratives is an important part of successful psychotherapy. In this view, several authors have highlighted the usefulness of narrating new experiences (like actions, thoughts, and stories) during therapy in contrast with maladaptive client self-narratives. These new experiences are termed here innovative moments (IMs), and different types can be specified: action, reflection, protest, reconceptualization, and performing change. With the aim of understanding which therapist skills are related to client IMs, we analyzed the association between exploration, insight, and action skills and IMs in two initial, two middle, and two final sessions of three good outcome (GO) and three poor outcome (PO) cases of emotion-focused therapy (EFT) for depression. IMs occurred more often in GO than PO cases. Furthermore, in GO more than PO cases, exploration and insight skills more often preceded action, reflection, and protest IMs in the initial and middle phases of EFT, but more often preceded reconceptualization and performing change IMs in the final phase. Action skills were more often associated with action, reflection, and protest IMs across all phases, especially in the final phase, of GO EFT.